PELAKSANAAN PUTUSAN NOMOR 206/PDT.G/2020/PN.PTK TENTANG PERKARA WANPRESTASI DALAM KONTRAK PERJANJIAN KERJA PENGADAAN ALAT INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) BALAI KESEHATAN MATA MASYARAKAT (BKMM) - NIM. A1011181122, RANA TSABITA (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstracIn the Contract of Work Agreement on the Procurement of Equipment for Waste Water Treatment Plants (IPAL) with a total contract value of Rp. 344,135,000 (Three Hundred Forty Four Million One Hundred Thirty Five Thousand Rupiah) between the Pontianak City Health Office and CV. Usring there has been a dispute between the two parties regarding the non-payment of the work that has been done, resulting in a decision number 206/Pdt.G/2020/PN.PTK. Implementation of decision number 206/PDT.G/2020/PN.PTK regarding the case of default in payments in the work agreement contract for the procurement of Waste Water Treatment Plant (IPAL) Public Eye Health Center (BKMM) between the Pontianak City Health Office and CV. Usring has binding legal force for both parties. The decision has permanent legal force (Incraht) which requires both parties to carry out the contents of the decision. Based on the above formulation, the writer formulates the research problem as follows: